Memórias e estratégias para a conservação do guigó-de-Sergipe (Callicebus coimbrai Kobayashi; Langguth, 1999) no estado de Sergipe - Souza, Marcelo Cardoso de (2013)
The present study describes the trajectory of protective actions of Sergipe‟s titi monkey (Callicebus coimbrai Kobayashi; Langguth, 1999), a primate endangered and endemic of Sergipe and Bahia states and proposes the use of computational biometrics to estimate their populations in the Atlantic Forest. It started from the principle that a primate newly described by science could influence the creation and increase the number of protected areas and that the algorithms used for verification of the identity of the human voice could be used for the identification of primate vocalization and assist in estimating the density of their populations in the Atlantic Forest. Within an interdisciplinary perspective, elaborated a synthesis of historical knowledge about this primate, joined strategy for their protection with conservation education and adopted the primate as flagship species. We also performed the correlation of the institutional aspects of biodiversity conservation at the international, national and local levels and the motivations for the creation of conservation units in Sergipe. We analyzed the theoretical aspects of the method of distance sampling, conventionally used for monitoring populations of primates and vocalizations were obtained to verify the identity of issuers. The hypothesis that the primate vocalization presents individual characteristics was validated and can be used to measure the distance from the emitter. It was found that the Conservation Education was fundamental to disseminate information about the Sergipe's biodiversity, in particular of the titi monkey (C. coimbrai) and facilitator of actions that contributed to the motivation and increase of primate researchs, for the involvement of institutions to protect the environment and the increase in protected areas. Recognized the significant importance of distance sampling to obtain data for estimating population density of species in tropical forests and found that the visualization of forest species as key to the study and census populations, especially through transects for counting by sightings, faces some difficulties, mainly in areas of dense vegetation and steep relief. Thus, biometrics can be applied as an auxiliary method for census and estimation of primates in tropical forests and allow conservationists use the resources presented here in addition to methods of transect and points or as an alternative to the census in areas where visualization is hampered by dense vegetation or steep relief. This perspective may imply the accuracy of the census of individuals in a population, in definition their conservation status, indication of areas for protection and guidance and subsidy to public policies, especially those related to the creation of protected areas.